Cost-effectiveness analysis of PET-CT-guided management for locally advanced head and neck cancer. (November 2017) - Smith, A.F.; Hall, P.S.; Hulme, C.T.; Dunn, J.A.; McConkey, C.C.; Rahman, J.K.; McCabe, C.; Mehanna, H.
Abstract: Background: A recent large United Kingdom (UK) clinical trial demonstrated that positron-emission tomography–computed tomography (PET-CT)-guided administration of neck dissection (ND) in patients with advanced head and neck cancer after primary chemo-radiotherapy treatment produces similar survival outcomes to planned ND (standard care) and is cost-effective over a short-term horizon. Further assessment of long-term outcomes is required to inform a robust adoption decision. Here we present results of a lifetime cost-effectiveness analysis of PET-CT-guided management from a UK secondary care perspective. Methods: Initial 6-month cost and health outcomes were derived from trial data; subsequent incidence of recurrence and mortality was simulated using a de novo Markov model. Health benefit was measured in quality-adjusted life years (QALYs) and costs reported in 2015 British pounds. Model parameters were derived from trial data and published literature. Sensitivity analyses were conducted to assess the impact of uncertainty and broader National Health Service (NHS) and personal social services (PSS) costs on the results. Results: PET-CT management produced an average per-person lifetime cost saving of £1485 and an additional 0.13 QALYs. At a £20, 000 willingness-to-pay per additional QALY threshold, there was a 75% probability that PET-CT was cost-effective, and the results remained cost-effective over the majority of sensitivity analyses. When adopting a broader NHS and PSS perspective, PET-CT management produced an average saving of £700 and had an 81% probability of being cost-effective. Conclusions: This analysis indicates that PET-CT-guided management is cost-effective in the long-term and supports the case for wide-scale adoption. Highlights: A Markov model was used to assess the impact of positron-emission tomography–computed tomography (PET-CT)-guided management for head and neck cancer. PET-CT was found to be cost-effective over a lifetime horizon from a United Kingdom secondary care perspective. PET-CT is expected to reduce per-patient secondary care lifetime costs by £1485. PET-CT is expected to increase per-patient quality-adjusted life years (QALYs) by +0.13 QALYs.